Solve: \( \frac{3}{b-7}+\frac{4}{b+7}=\frac{42}{b^{2}-49} \) \( b=\square \) (Enter your answers, separated by commas, or type DNE if no solution exists)
Solución de tutoría real
Responder
Solución
¡Inicia sesión para desbloquear respuestas gratis!
Una plataforma de aprendizaje en la que confían millones de estudiantes y profesores reales.
Revisado y aprobado por el equipo de tutoría de UpStudy
Extra Insights
To solve the equation \( \frac{3}{b-7}+\frac{4}{b+7}=\frac{42}{b^{2}-49} \), we first notice that \( b^2 - 49 \) can be factored as \( (b-7)(b+7) \). Therefore, we can rewrite the right-hand side of the equation: \[ \frac{3}{b-7}+\frac{4}{b+7}=\frac{42}{(b-7)(b+7)} \] Next, we can combine the fractions on the left side: The common denominator for the fractions on the left side is \( (b-7)(b+7) \). Thus, we rewrite it: \[ \frac{3(b+7) + 4(b-7)}{(b-7)(b+7)} = \frac{42}{(b-7)(b+7)} \] Now, we simplify the numerator: \[ 3(b+7) + 4(b-7) = 3b + 21 + 4b - 28 = 7b - 7 \] This allows us to rewrite the equation as: \[ \frac{7b - 7}{(b-7)(b+7)} = \frac{42}{(b-7)(b+7)} \] Since the denominators are the same (as long as \( b \neq 7 \) and \( b \neq -7 \)), we can equate the numerators: \[ 7b - 7 = 42 \] Now, we solve for \( b \): \[ 7b = 42 + 7 \] \[ 7b = 49 \] \[ b = 7 \] However, we need to remember that \( b \neq 7 \) or \( b \neq -7 \) because of the restrictions from the original equation. So \( b = 7 \) does not satisfy the equation. Now let’s check \( b = -7 \): Substituting \( b = -7 \): \[ \frac{3}{-7-7}+\frac{4}{-7+7} \quad \text{(undefined)} \] Again, \( b = -7 \) is also not a solution. Since both potential solutions are not valid due to the restrictions we found, we conclude: There is no solution. Final answer: DNE